REAKSI HARGA SAHAM DI PASAR MODAL INDONESIA TERHADAP PERISTIWA TEROR BOM PERIODE 2002-2017 - Carissa Cindy Febiana; Noorlailie Soewarno (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2017)
This research aims to determine the reaction of stock prices in Indonesia stock ecxchange when event of terror bombs. This research use event study where observation to window period of abnormal return during 5 days before, event date, and 5 days after the event. The data was collected from the Indonesia stock exchange by using daily closing price of stock price and JCI (Jakarta Composite Index). The population are event of terror boms period 2002-2017. The sampling technique in this research used purposive sampling with the criterias are the largest number of victims and the availability of data.The statistic instrument test has been done by using paired sample t-test and SPSS 24 program. The results show that there is the effect of bomb terrorism on stock price reaction in Indonesia stock exchange indicated by the differences of abnormal return. The influential incident that occurred during the bombing of Indonesia's history in Bomb Bali I at 2002, with the passage of time and the number of bombing events, investors have been sensitive to the occurrence of bomb explosion events against stock prices in the Indonesian capital market. Keywords: Event study, terror boms, abnormal return, Indonesia stock exchange